Anisotropy-dependent seaweed growth during directional solidification of Al-4.5%Cu single crystal. (September 2020) - Wang, Yumin; Li, Shuangming; Liu, Zhenpeng; Yang, Bin; Zhong, Hong; Xing, Hui
Abstract: Three seaweed patterns, axial seaweed, titled seaweed, and degenerate seaweed were acquired from the various growth directions on the 111 planes of an Al-4.5% Cu single crystal. The inherently ordered crystal, with a seemingly disordered morphology, was investigated using back-reflection Laue (BRL) pattern and electron backscattered diffraction (EBSD). Microstructural characterization of the crystal indicated that the growth orientation of the seaweed could be linked to the crystallographic direction 〈011〉, having a favorable order. The formation of those three seaweed morphologies is sensitive to the anisotropy of the surface tension or interface stiffness caused by the six-fold symmetry of the crystal. Graphical abstract: Image, graphical abstract